2014
DOI: 10.1038/ncomms5099
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes arise from multiple lineages that are heterogeneously and dynamically distributed

Abstract: Adipose tissue development is poorly understood. Here we use a lineage-tracing strategy optimal for adipocytes to provide evidence that Myf5 precursors are not the exclusive source of brown adipocytes and contribute more to the mature white and brite adipocyte populations than previously thought. Moreover, Myf5 lineage distribution in adipose tissue changes in response to modifiable and non-modifiable factors. We also find that the Pax3 lineage largely overlaps with the Myf5 lineage in brown fat and subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
313
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(335 citation statements)
references
References 28 publications
16
313
0
6
Order By: Relevance
“…Moreover, studies that observed adipogenic differentiation of MPs identified the myogenic progenitors by labelling for Pax7 or the myogenic regulatory factor Myf5. However, recent studies showed that Myf5 can be more widely distributed than previously appreciated and also labels white adipocytes 28. Moreover, a subpopulation of Myf5 + cells from extraocular muscle expresses Sca1 and is adipogenic 50.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, studies that observed adipogenic differentiation of MPs identified the myogenic progenitors by labelling for Pax7 or the myogenic regulatory factor Myf5. However, recent studies showed that Myf5 can be more widely distributed than previously appreciated and also labels white adipocytes 28. Moreover, a subpopulation of Myf5 + cells from extraocular muscle expresses Sca1 and is adipogenic 50.…”
Section: Discussionmentioning
confidence: 98%
“…Although an endothelial origin for adipocytes could contradict the work of Seale and colleagues and Sanchez-Gurmaches and colleagues, describing adipocytes arising from Myf5 + myogenic precursors (Sanchez-Gurmaches and Guertin, 2014b;Seale et al, 2008;Tran et al, 2012), De Angelis and colleagues reported the existence of progenitor cells from embryonic dorsal aorta, expressing both endothelial (including VE-cadherin) and myogenic markers (i.e. Myf5) (De Angelis et al, 1999).…”
Section: Endothelial Cellsmentioning
confidence: 94%
“…It is well established that Myf5-Cre targets cells that give rise to skeletal muscle and interscapular BAT (iBAT) (Seale et al, 2008). Myf5-Cre also targets interscapular WAT (iWAT) and retroperitoneal WAT (rWAT) but not inguinal WAT (ingWAT) or perigonadal WAT ( pWAT) (Sanchez-Gurmaches and Guertin, 2014;Sanchez-Gurmaches et al, 2012). Myf5-Cre;PDGFRα +/D842V mutants (hereafter referred to as Myf5-D842V) were viable, although an overall smaller body size became apparent around postnatal day (P)5.…”
Section: Pdgfrαmentioning
confidence: 99%